Properties of tantalum oxynitride thin films produced by magnetron sputtering: the influence of processing parameters - Cristea, D. (2014)
The main purpose of this work is to present and to interpret the change of structure and physical properties of tantalum oxynitride (TaNxOy) thin films, produced by dc reactive magnetron sputtering, by varying the processing parameters. A set of TaNxOy films was prepared by varying the reactive gases flow rate, using a N2/O2 gas mixture with a concentration ratio of 17:3. The different films, obtained by this process, exhibited significant differences. The obtained composition and the interpretation of X-ray diffraction results, shows that, depending on the partial pressure of the reactive gases, the films are: essentially dark grey metallic, when the atomic ratio (N + O)/Ta < 0.1, evidencing a tetragonal β-Ta structure; grey-brownish, when 0.1 < (N + O)/Ta < 1, exhibiting a face-centred cubic (fcc) TaN-like structure; and transparent oxide-type, when (N + O)/Ta > 1, evidencing the existence of Ta2O5, but with an amorphous structure. These transparent films exhibit refractive indexes, in the visible region, always higher than 2.0. The wear resistance of the films is relatively good. The best behaviour was obtained for the films with (N + O)/Ta ≈ 0.5 and (N + O)/Ta ≈ 1.3.